Who’s for dinner? High-throughput sequencing reveals bat dietary differentiation in a biodiversity hotspot where prey taxonomy is largely undescribed - Burgar, J.; Murray, D.; Craig, M.; Haile, J.; Houston, J.; Stokes, V.; Bunce, Michael (Wiley-Blackwell Publishing, 2014)
Effective management and conservation of biodiversity requires understanding of predator–prey relationships to ensure the continued existence of both predator and prey populations. Gathering dietary data from predatory species, such as insectivorous bats, often presents logistical challenges, further exacerbated in biodiversity hot spots because prey items are highly speciose, yet their taxonomy is largely undescribed. We used high-throughput sequencing (HTS) and bioinformatic analyses to phylogenetically group DNA sequences into molecular operational taxonomic units (MOTUs) to examine predator–prey dynamics of three sympatric insectivorous bat species in the biodiversity hotspot of south-western Australia. We could only assign between 4% and 20% of MOTUs to known genera or species, depending on the method used, underscoringthe importance of examining dietary diversity irrespective of taxonomic knowledge in areas lacking a comprehensive genetic reference database. MOTU analysis confirmed that resource partitioning occurred, with dietary divergence positively related to the ecomorphological divergence of the three bat species. We predicted that bat species’ diets would converge during times of high energetic requirements, that is, the maternity season for females and the mating season for males. There was an interactive effect of season on female, but not male, bat species’ diets, although small sample sizes may have limited our findings. Contrary to our predictions, females of twoecomorphologically similar species showed dietary convergence during the mating season rather than the maternity season. HTS-based approaches can help elucidate complex predator–prey relationships in highly speciose regions, which should facilitate the conservation of biodiversity in genetically uncharacterized areas, such as biodiversity hotspots.